Effect of Molding Methods on Free-Thaw Durability of Pervious Concrete. Issue 1 (1st January 2023) - Li, Qiuxiang; Zheng, Jie; Fu, Mingfu
Abstract: Pervious concrete is one of the most important new materials in the sustainable development of infrastructure construction, and has been widely studied and developed by the industry. Through freeze-thaw test, dynamic elastic modulus test, mass test and strength test, the durability of pervious concrete with different molding methods was studied. The test results show that the mass loss rate and strength decline rate of the pervious concrete controlled by the pervious rate are the lowest after 25 cycles of freezing and thawing, marshall compacted pervious concrete has the lowest loss rate of dynamic elastic modulus, and plug-in concrete has the lowest durability. Finally, the mix proportion of pervious concrete with optimal target porosity by rotary compaction is suggested.